An interoperable software ecosystem to store, visualize, and publish water resources systems modelling data. (May 2022) - Abdallah, Adel M.; Rheinheimer, David E.; Rosenberg, David E.; Knox, Stephen; Harou, Julien J.
Abstract: Water systems modelers have developed multiple, independent, model- and study-area specific tools to store, query, visualize, and share their data. This fragmentation makes difficult comparisons, and synthesis within or across study areas. This paper identifies the common components of four existing tools for data storage, web visualization, and repository, and relates them correctly in syntax and semantics. Connecting the tools in a state-of-the-art, open-source software ecosystem allowed comparing the effects of population growth and water conservation in simulation and optimization models for the Bear River Watershed, U.S. and Monterrey, Mexico that have different spatial coverage and urban and agricultural representations. The software ecosystem also publishes the models and their data for discovery. The software ecosystem can help modelers tap the best features of individual software tools to answer a next generation of water management questions that seek to discover, use, reproduce, extend, compare, or synthesize within or across study areas. Highlights: We built a software ecosystem to visualize, compare, edit, run, and publish data, models, and scenarios for multiple water systems models. The software ecosystem encourages reuse of tools and reproducibility of analysis. The software is demonstrated using three models in the Bear River Watershed, U.S, and in Monterrey, Mexico.